PENGARUH SELF EFFICACY TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIK SISWA SMP - Hari, Laela Vina; Zanthy, Luvy Sylviana; Hendriana, Heris (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
The purpose of this research is to analyze and examine in depth about the influence of self-efficacy on the ability to think critically mathematically of junior high school students. The research method used in this research is the correlational method with the quantitative approach using simple of 30 students of junior high school class VIII in one of junior high school in West Bandung Regency with high, medium, and low ability student classification. The instrument used consisted of the test of critical thinking ability of mathematics as much as 7 item and non-test in the form of the self-efficacy scale as many as 24 statement. The results of this study indicate that the ability to think critically mathematically junior high school students are positively influenced by self-efficacy amount 56,4 % and influenced by other factors of students self-efficacy amount 43,6 %.